Domain analysis as a theoretical-methodological perspective in knowledge organization: an analysis of theoretical aspects in international literature - Guimarães, José Augusto Chaves [UNESP] (Biblioteca Central da UNB, 2024)
Introduction: Domain analysis (DA) allows the identification and analysis of significant knowledge in a field of knowledge (trends, patterns, processes, agents and their relationships), constituting an important methodological source for Knowledge Organization (KO) in the field of Information Science. This presupposes interpretation, which can only be applied and understood in a given context, because domains have their own system for the creation and structuring of new knowledge, theories and methodologies.Objective: The aim of this study was to analyze the international literature produced in English on theoretical issues of DA in the context of KO in order to provide a configuration of this field of study with regard to the elements that integrate and characterize it. Methodology: Characterized as a theoretical investigation, this study carried out a critical literature review, through content analysis, of a corpus composed of theoretical classic texts on the subject published in various sources and of articles contained in special issues on the subject of domain analysis. Results: It was possible to systematize the concepts found in the analyzed literature regarding Origins, Definition, Nature, Object, Importance/Contributions/Effects, Approaches, Paradigms, Parameters/Axes, Stages/Sources/Dimensions, Epistemic Stances, Interdisciplinary Character, and Supporting Theories/Disciplines, allowing a metatheoretical configuration of this field of knowledge. Conclusions: a) DA occupies a central position in the sociocultural perspective of KO because it provides a theoretical-methodological framework for the development of processes, for the construction and application of instruments and for the generation of products; b) The concept of domain is broad and multifaceted, and can encompass subjects, fields of knowledge, institutions and many other aspects necessary for the characterization of a given context and its dynamics; c) Birger Hjørland reveals a seminal character and occupies a central position in relation to DA in KO; d) DA currently faces the challenge of encompassing multi, inter and transdisciplinary knowledge; e) the research, through a critical review of literature on DA, using content analysis, provided a first metatheoretical approach to the topic, by identifying and systematizing, in the specialized literature, elements related to schools of thought, theories, interacting disciplines, invisible schools and historical roots, among other aspects.
El análisis de dominio como perspectiva teórico-metodológico en la organización del conocimiento: un análisis de aspectos teórico
A análise de domínio como perspectiva teórico-metodológica na organização do conhecimento: uma análise dos aspectos teóricos na literatura internacional
Keywords: Content analysis; Domain-analysis; Information Science; Knowledge Organization